The Edinburgh variant of a talar body fracture: a case report - Biant Leela C; Phillips Sally-Ann; Clement Nicholas D (Journal of Orthopaedic Surgery and Research, 2010)
Abstract We describe a novel closed pantalar dislocation with an associated sagittal medial talar body and medial malleolus fractures. Closed reduction was attempted unsuccessfully. Open reduction was performed, revealing a disrupted talonavicular joint with instability of the calcaneocuboid joint. This configuration required stabilisation with an external fixator. There were no signs of avascular necrosis, or arthrosis at 15 months follow but is currently using a stick to mobilise.